1981
DOI: 10.1073/pnas.78.1.621
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human diferric transferrin with reticulocytes.

Abstract: Methods have been devised for preparing human transferrin with a different isotope ofiron selectively labeling each of the two iron binding sites and for determining the distribution of radioiron among transferrin molecules. When diferric human transferrin was exposed to human or animal reticulocytes, there was an equal contribution of radioiron from the acid-stable and acid-labile sites. In this delivery, both atoms ofiron were removed simultaneously from the diferric transferrin molecule, converting it to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…The separation procedure by means of gel chromatography on Sephacryl S200, ion exchange chromatography on DEAE Sephacel, and conversion of the diferric into the apotransferrin form was the same as described for human transferrin (4). Isolation of apo-, mono-, and diferric transferrin was carried out by isoelectric focussing procedures identical to those described for human transferrin (3,4). In this instance, the starting material was 200 mg of rabbit apotransferrin one-third saturated with 55Fe or 59Fe-tagged ferrous ammonium sulfate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The separation procedure by means of gel chromatography on Sephacryl S200, ion exchange chromatography on DEAE Sephacel, and conversion of the diferric into the apotransferrin form was the same as described for human transferrin (4). Isolation of apo-, mono-, and diferric transferrin was carried out by isoelectric focussing procedures identical to those described for human transferrin (3,4). In this instance, the starting material was 200 mg of rabbit apotransferrin one-third saturated with 55Fe or 59Fe-tagged ferrous ammonium sulfate.…”
Section: Methodsmentioning
confidence: 99%
“…Transferrin was isolated from 275 ml normal rabbit plasma after iron saturation with ferrous ammonium sulfate under spectrophotometric control (3). The separation procedure by means of gel chromatography on Sephacryl S200, ion exchange chromatography on DEAE Sephacel, and conversion of the diferric into the apotransferrin form was the same as described for human transferrin (4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The labelling of the transferrin was always done in the presence of serum. FeS04 (0.1 M) is well known (Huebers et al, 1981) to be a very efficient donor of iron to transferrin. We also confirmed that, in our hands.…”
Section: The Provision Of Extracellular Iron To the Intracellularmentioning
confidence: 99%